High concentration Eu3+ doped yttria-stabilized zirconia ceramics; Optik; Vol. 295 - Valiev D. T. Damir Talgatovich; Stepanov S. A. Sergey Aleksandrovich; Dvilis E. S. Edgar Sergeevich; Paygin V. D. Vladimir Denisovich; Khasanov O. L. Oleg Leonidovich (2023, 2023)
The series of yttria-stabilized zirconia (YSZ) ceramics doped with high Eu3+ ions concentration (up to 15 wt%) were successfully fabricated by Spark Plasma Sintering (SPS) technique for the first time. The effect of europium concentration and atmospheric annealing on the optical, structural, and luminescent properties has been studied in detail. The combination of XRD and EDS data allows to find two phases in tested YSZ:Eu ceramics such as ZrO2 and Zr2O. The highest transmission values were achieved about 63% at 600 nm for the 10 wt% of Eu2O3 doped YSZ ceramics without annealing. When the annealing temperature changes from 1300◦ to 1600◦C the transmission values increase to 70%. An analysis of the photoexcitation and photoluminescence spectra showed that the main excitation bands are determined by the direct excitation of the 7 F0 ground state to higher 4 f levels with following radiation transitions in Eu3+ ions. The optimal Eu3+- dopant concentration in YSZ ceramics was established and the process of emission quenching was discussed. The luminescence decay kinetics are approximated by the single or sum of two exponential functions in dependence of Eu3+ ions concentrations.